2016
DOI: 10.1186/s13014-016-0710-y
|View full text |Cite
|
Sign up to set email alerts
|

Target delineation and optimal radiosurgical dose for pituitary tumors

Abstract: Stereotactic radiosurgery (SRS) delivered as either single-fraction or multi-fraction SRS (2–5 fractions) is frequently employed in patients with residual or recurrent pituitary adenoma. The most common delivery systems used for SRS include the cobalt-60 system Gamma Knife, the CyberKnife (CK) robotic radiosurgery system, or a modified conventional radiotherapy machine (linear accelerator, LINAC). Tumor control and normalization of hormone hypersecretion have been reported in 75–100 % and 25–80 % of patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 143 publications
(240 reference statements)
0
42
0
Order By: Relevance
“…In most centers, a margin of 0 to 1 mm is generally used for GTV to the planning tumor volume (PTV) expansion. 37 Discrimination between the lesion and the normal pituitary was difficult to perform in our patient with LH, and the PTV took into account potential microscopic lymphocytic infiltration. The target for SRS in our patient was the entire intrasellar area, and a 15-Gy marginal dose was used.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In most centers, a margin of 0 to 1 mm is generally used for GTV to the planning tumor volume (PTV) expansion. 37 Discrimination between the lesion and the normal pituitary was difficult to perform in our patient with LH, and the PTV took into account potential microscopic lymphocytic infiltration. The target for SRS in our patient was the entire intrasellar area, and a 15-Gy marginal dose was used.…”
Section: Discussionmentioning
confidence: 93%
“…SRS is a radiation therapy technique that allows more precise target localization, accurate dose delivery, and a reduced amount of normal tissue treated with high doses of radiation compared with conventional radiotherapy. 37 This technique precisely delivers a high dose of irradiation to welldefined small to moderate-volume targets using either singlefraction or multi-fraction SRS (2-5 fractions). The most common delivery systems used for SRS include the cobalt-50 system Gamma Knife, the CyberKnife Robotic Radiosurgery System, or a modified conventional radiotherapy machine (LINAC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, endocrinological remission was not achieved 4 years after GKRS. The effect of SRS has been reported in the treatment of recurrent functioning PA 5,9) . Mouslech et al 12) reported a case of endocrinological remission of GKRS for recurrent TSH-PA.…”
Section: Discussionmentioning
confidence: 99%
“…For over one decade patients with pituitary adenoma have been treated primarily with two parallel opposed fields or a three field technique [1][2][3][4][5][6][7]. Only a few recent publications describe the application of intensity modulated radiotherapy (IMRT) or volumetric modulated arc (VMAT) technique in this region [8][9][10], none of them mentioning the flatness filter free (FFF) mode. FFF is applicable in combination with fluence modulating techniques like IMRT or VMAT.…”
Section: Introductionmentioning
confidence: 99%